THE ROLE OF CHRONIC POLYPOID RHINOSINUSITIS IN OCCURRENCE OF MALIGNANT EPITHELIAL TUMORS OF THE PARANASAL SINUSES AND THE NASAL CAVITY - M. Yu. Vereshchagin; A. U. Minkin; L. S. Khodasevich (Опухоли головы и шеи, 2015)
Growth of occurrence of malignant epithelial tumors of the nasal cavity (NC) and the paranasal sinuses (PNS) is noted. Absolute majority of patients come for treatment with the III and the IV stage of the disease. No trend for decreasing of the untreatedness parameter is observed. Increasing of the efficiency of treatment of patients with cancer depends on timely diagnostics. The main reason of late diagnostics is insufficient oncological alertness of doctors in polyclinics. The issues of therapy tactics at the stage of pre-tumor diseases of the NC and the PNS remain unsolved, while background process that precede development of cancer are morphologically revealed with 56.7 % of patients. One of the most frequently occurred background development processes of the NC and the PNS cancer is chronic polypoid rhinosinusitis (CPR). The degree of occurrence of CPR is high, and the annual growth of its incidence by 2 to 4 % has been observed for the previous 10 years. There are only certain works that view CPR as a pre-cancer disease.The objective of the study is improvement of results of early diagnostics of cancer and optimization of the surgical tactics with pre-cancer diseases of the upper jaw and the PNS.Materials and methods. Retrospective and prospective clinical and morphological analysis of data of 58 patients with benign polypous changes (BPC) and of 182 patients with malignant epithelial tumors (MET)  of the NC and the PNS treated at the Arkhangelsk Regional Clinical Oncology Dispensary from 1980 to 2010 has been performed.Results and discussion The maximum number of patients in both groups is at the age category from 40 to 59 years. Besides, the average age of patients with the BPC was lower than that of the patients with the MET (45.6 ± 2.3 and 54.0 ± 1.5 years old, respectively).Patients of working age prevailed both in the group with the BPC and the group with the MET of the NC and the PNS (19.0 / 81.0 % and 39.6 / 62.1 %, respectively). Males prevailed in the group with the BPC (53.4 % of males and 46.6 % of females), and females prevailed in the group with the MET (39.6 % of males and 60.4 % of females). However, we believe that this controversy to our hypothesis is explained with greater life expectancy of females (females are the prevailing majority in the groups of age category of 70 to 89 years old: 19.8 % are females, 5.3 % are males).The prevailing number of patients with the BPC (77.6 %) lived in cities, and such number in the group of patients with the MET was 54.9 %. The most frequent type of operative treatment of patients with the BPC was electrical maxillar ethmoidectomy that was performed in 82.9 % of cases. Relapse after performance of electrical maxillar ethmoidectomy was demostrated by 2 patients which comprised 4.3 %.In significant number of cases (70,6 % in the group with the BPC and 65.9 % in the group with the MET), the pathological process was localized in the maxillar cavity. Most frequently, glandular-fibrous polyps were revealed (42.1 %), and this morphological structure prevaled with male patients (57.9 % with males and 26.3 % with females); MET of the NC and the PNS, in their turn, also more frequently occurred with males.In 69.0 %, the CPR has been the background for severe epithelial dysplasia, and the CPR, in its turn, was reveled with 39.8 % of patients with the MET.Conclusion. We believe that the data provided prove the key role of the CPR in development of MET of the NC and the PNS.